few remarks on the change in the legal classification of an act in the course of court proceedings on the basis of the institution of an ideal confluence of prohibited acts (Discourse of Law and Administration, 2021)
A few remarks on the change in the legal classification of an act in the course of court proceedings on the basis of the institution of an ideal confluence of prohibited acts. The publication contains considerations on changing the legal classification of an act in the course of court proceedings. These considerations concern the change of the legal picture of an act on the basis of the institution of the ideal confluence of prohibited acts. Multiple valuation of the same act from the point of view of the Criminal Code and the Fiscal Penal Code influences the extension of the criminal law consequences borne by the accused for this act.
Keywords: criminal law; legal classification of an act in the course of court proceedings; ideal confluence of prohibited acts; Fiscal Penal Code